2019
DOI: 10.1186/s12886-019-1177-z
|View full text |Cite
|
Sign up to set email alerts
|

Foveal avascular zone and macular vessel density after correction for magnification error in unilateral amblyopia using optical coherence tomography angiography

Abstract: Background To investigate the area of foveal avascular zone (FAZ) and macular vessel density (VD) after correction for magnification error in unilateral amblyopia using optical coherence tomography angiography (OCTA). Methods Participants comprised 15 patients with unilateral amblyopia due to anisometropia with or without strabismus (mean age, 9.8 ± 3.4 years; range, 6–17 years). OCTA images were obtained by using spectral-domain OCT with angiography software. The OCTA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 24 publications
5
55
2
Order By: Relevance
“… 6 Considering the long exposure time and the requirement of dye use in other imaging methods such as FA, OCTA presents a useful and easy way of detecting retinal and optic disc pathologies, especially in pediatric cases. 9 …”
Section: Discussionmentioning
confidence: 99%
“… 6 Considering the long exposure time and the requirement of dye use in other imaging methods such as FA, OCTA presents a useful and easy way of detecting retinal and optic disc pathologies, especially in pediatric cases. 9 …”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy may be due to the middle location of DCP in the retinal layer where is more distal from the retinal arterial and choroidal circulations 11 , a larger ROI may be needed to detect the positive changes in DCP. Moreover, Araki 10 and Demirayak 9 found no change of vessel density in SCP and DCP and a shrink FAZ area of SCP, whereas Sobral 7 reported an enlarged FAZ of SCP and DCP. The inconsistency among these studies could result from the mixture of types of amblyopia in these studies, which used the fellow eyes or the BCVA equal to 20/20 as normal controls instead of healthy subjects or didn’t pay special attention to differences in AL of amblyopic eyes 7 , 9 which are often hyperopic and small that can cause decreased vessel density 12 , 13 in the data analysis.…”
Section: Discussionmentioning
confidence: 98%
“…More recently, the advent of optical coherence tomographic angiography (OCTA), a noninvasive in vivo neuroimaging modality, has enabled researchers to investigate the retinal microvasculature changes associated with human amblyopes [5][6][7][8][9][10] . Part of these studies have shown reduced vessel density in the macular area associated with amblyopia compared to that of fellow eyes and/or controls [5][6][7][8] , yet others reported no change of vessel density 9,10 . A few studies also indicated that mixing different types of amblyopia could confound the observations and result in inconsistency among the studies 8,10 .…”
Section: Effect Of Amblyopia Treatment On Macular Microvasculature Inmentioning
confidence: 99%
“…There are many OCTA studies in fundus diseases; however, in terms of amblyopia, there are fewer studies [21][22][23]. In addition, in terms of strabismus amblyopia [24], most of the research results show no signi cant difference between amblyopia eyes and healthy eyes in terms of the capillary plexus vascular density of the macular fovea.…”
Section: Discussionmentioning
confidence: 99%